(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: The search to evidence a link between the molecular markers (IL-8) with colorectal cancer. The aimof the presented work is examining the relation regarding the biomarker (IL-8) in colorectal cancer (CRC)tissues as well as its relation with the other clinic pathological variables.Methods: The detection of IL-8was confirmed using histopathological examination of colonic biopsy oftissue section fixed on slides previously coated and analyzed by immunohistochemistry method (IHC),hence to detect the variable regarding IL-8 expression in normal as well as CRC tissues including (adjacentnormal tissue and healthy controls tissues); in addition to its association with other clinic-pathologicalvariables (intensity, gender and age).The results of the study specified the enrichment regarding IL-8 expression in the samples of CRC with theuse of IHC approach. No considerable relation has been indicated between the expression of IL-8 with theother clinical-pathological variables (gender and age), yet there has been considerable relation between theexpression of IL-8 and the stain’s intensity (grade), while it has been increased in tissues of CRC; this mightbe specified as one of the risk factors with regard to the CRC’s development and the metastasis in the samplesof CRC, also it might be significant marker to predict insignificant prognosis in patients experiencing CRC,also it can be utilized as possible therapeutic target in the CRC.